1994
DOI: 10.1177/027112149401400108
|View full text |Cite
|
Sign up to set email alerts
|

Home-based Descriptive and Experimental Analysis of Problem Behaviors in Children

Abstract: The authors conducted descriptive and experimental analysis of problem behaviors in the homes of 5 children. The children's parents were actively involved in the descriptive assessment and manipulated potential controlling variables during the experimental analysis. The information obtained from each functional assessment method (e.g., behavioral interview, direct observation assessment, experimental analysis) indicated the same function for each child's problem behavior. Based upon the results of the descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 21 publications
2
62
1
Order By: Relevance
“…In all cases, effective suppression of aberrant behavior was achieved and positive social behavior emerged. These results replicate previous studies on maintenance of FCT (Durand & Carr, 1992;Northup et al, 1994) and previous studies on the application of these procedures in home (Arndorfer et al, 1994) and school Durand & Carr, 1991Northup et al, 1994;Sasso et al, 1992) settings. In this study, parents conducted all procedures effectively with only intermittent consultation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In all cases, effective suppression of aberrant behavior was achieved and positive social behavior emerged. These results replicate previous studies on maintenance of FCT (Durand & Carr, 1992;Northup et al, 1994) and previous studies on the application of these procedures in home (Arndorfer et al, 1994) and school Durand & Carr, 1991Northup et al, 1994;Sasso et al, 1992) settings. In this study, parents conducted all procedures effectively with only intermittent consultation.…”
Section: Resultssupporting
confidence: 90%
“…al., 1994;Wacker et al, 1990). The results of these studies have led to applications of these treatments in schools (Northup et al, 1994) and homes (Arndorfer, Miltenberger, Woster, Rortvedt, & Gaffaney, 1994). As we begin to apply FCT to less controlled settings, the results of both descriptive (Mace & Lalli, 1991) and experimental (Iwata, Dorsey, Slifer, Bauman, & Richman, 1982 analyses are needed to develop effective treatment.…”
mentioning
confidence: 99%
“…However, practical knowledge about the ways to conduct functional assessments effectively within family environments, either by clinicians or families themselves, is limited. Notable exceptions are the works of Albin et al (1996), , and Arndorfer, Miltenberger, Woster, Rortvedt and Gaffaney (1994). Arndorfer et al (1994) demonstrated that parents successfully implemented functional assessments in natural settings; whereas reported that parents typically were able to identify the function of the behaviour quite rapidly.…”
Section: General Conclusionmentioning
confidence: 99%
“…Notable exceptions are the works of Albin et al (1996), , and Arndorfer, Miltenberger, Woster, Rortvedt and Gaffaney (1994). Arndorfer et al (1994) demonstrated that parents successfully implemented functional assessments in natural settings; whereas reported that parents typically were able to identify the function of the behaviour quite rapidly. Nevertheless, further research in the development and testing of "friendly" practical packages of assessment information for parents to use within home environments is clearly needed.…”
Section: General Conclusionmentioning
confidence: 99%
“…These data suggest that the scatter plot is used as an assessment tool in clinical practice, in spite of the fact that no replications of the Touchette et al (1985) findings have appeared in the literature. Although reference to the use of the scatter plot can be found in a number of studies (Arndorfer, Miltenberger, Woster, Rortvedt, & Gaffaney, 1994;Cameron, Luiselli, Littleton, & Ferrelli, 1996;Durand & Kishi, 1987;Kennedy & Itkonen, 1993;Kennedy & Souza, 1995;Lalli et al, 1993;Linscheid, Iwata, Ricketts, Williams, & Griffin, 1990;Ricketts et al, 1993Ricketts et al, , 1994, none of those reports presented the actual data. Thus, the extent to which behavior problems show temporal characteristics such as those observed for 2 of the participants in the Touchette et al study remains largely unknown.…”
mentioning
confidence: 99%